Business Identification Number: Socialization and Assistance for MSME Actors in Malang - Rismawati Rismawati; Farida Idayati; Yuliastuti Yuliastuti; Dian Arini (Trescode Green Organization, 2024)
This activity aims to evaluate the effectiveness of socialization and mentoring activities in managing Business Identification Numbers (NIB) in Singosari District, Malang, East Java. The main objective is to increase the understanding and awareness of Micro, Small, and Medium Enterprises (MSMEs) about the importance of business legality and NIB management procedures. This activity was carried out from January to March 2024 involving 20 MSMEs and led by lecturers from the Indonesian School of Economics, Surabaya. The method includes socialization and individual consultation sessions to provide practical information and direct guidance in managing NIB. Evaluation using a qualitative approach shows that socialization and mentoring activities are effective in increasing the understanding and confidence of MSMEs in managing NIB. Participants experienced an increase in knowledge about the benefits of NIB, such as access to financing and opportunities for participation in government programs. However, there are limitations in the accessibility and sustainability of the program. Suggestions for the future include expanding the reach of socialization, strengthening cooperation, and utilizing technology to support the sustainable growth of MSMEs in the region. This activity makes a positive contribution to supporting MSMEs in managing their businesses legally and sustainably in Singosari District.